Meningkatkan Kompetensi Pedagogik Guru Non Akademik dalam Penyusunan Rencana Pelaksanaan Pembelajaran Harian (RPPH) Melalui Supervisi Akademik Kepala Sekolah di TK Negeri 1 Jereweh Tahun Pembelajaran 2018/2019 - Hosniwati (Jurnal LENTERA: Jurnal Studi Pendidikan, 2020)
This research is motivated by the lack of cognitive abilities in recognizing the shapes and colors of objects in Group B TK Negeri 1 Jereweh, and varied games are rarely applied to the cognitive development of children. The formulation of the problem in this study is: "How to improve cognitive abilities in introducing shapes and colors of objects with the varied play of children of Group B in Jereweh State Kindergarten 2018/2019 learning year?" objects with Group B children's varied games in Jereweh State Kindergarten 1 2018/2019 learning year. This type of research is Classroom Action Research (CAR), with 4 stages of action namely: planning, action implementation, observation, and reflection. The number of subjects in this study was 3 people. Data collection methods used are the method of observation and documentation. Analysis of the data used in this study is a qualitative descriptive analysis. Through Academic Supervision the principal can be concluded that: 1). In the components of the formulation of learning objectives indicators, seen an increase from 40% in the initial ability, to 60% in cycle 1 and increased to 70% at the end of the activity. 2). In the Determination Component of learning materials and materials, there is an increase in ability from 65% to 70% after cycle 1 and is stronger to 80%. 3). In the Component Selection Strategy and learning method, which includes learning steps and determining the allocation of time used, seen a significant increase from the original only 40% to 60% in cycle 1 and increased again to 75% after cycle 2. 4 ). Although there was no noticeable increase, in the selection component of the media and learning tools there was also an increase from 60% at the beginning of the activity and after cycle 1, to 80% after cycle 2